Neuroeducation strategies that promote participation in the classroom. A belief from the experience of university students in Perú - Copaja, Christian Alberto Yaya; Vera, Juan Raúl Egoavil (Edelweiss Applied Science and Technology, 2025)
This study’s purpose was to describe university students’ beliefs from their experience using neuroeducation strategies that promote participation during classes. This study was conducted in a qualitative paradigm and used a phenomenological method to understand the beliefs and experiences of students. Data were gathered through interviews based on a script, involving participants from a Digital Animation course at two Peruvian universities. Five neuroeducation strategies were implemented, focusing on understanding their impact on participation. The findings revealed that students show a favorable belief of these strategies; particularly valuing gamification, as it allows students to engage playfully in class activities, improving their performance. However, cooperative learning presented challenges, because of the low levels of participation and lack of commitment from some group members. The conclusion of this study is that neuroeducation strategies promote participation and performance when applied with balance and suitably to student needs. Teachers have a significant role as facilitators to promote participation in classes, by applying these strategies to create an engaging environment for learning. Practical implications emphasize the significance of integrating gamification into teaching strategies to promote participation and addressing group dynamics in cooperative learning to ensure fair contribution. These insights can be valuable for teachers and institutions in implementing effective neuroeducation strategies.